Characterization of Sardinian Bentonite - Mannu, A.; Vlachopoulou, G.; Sireus, V.; Mulas, G.; Petretto, G. L. (Journal of Scientific Research, 2019)
The employment of clays in industry and on laboratory scale is still of interest, despite their long history. The chemical-physical characteristics of such materials are strongly related to their geographical origin and the availability of proper characterization techniques is of great importance in order to gain as more information about their behavior when utilized as filling materials. In the present contribution, a physical characterization by meaning of Thermogravimetry and N2 physisorption analyses of samples of bentonite collected from the deposit of S´Aliderru in the north of Sardinia (Italy) is reported.